Early effective treatment may protect from cognitive decline in paediatric multiple sclerosis - Johnen, A.; Elpers, C.; Riepl, E.; Landmeyer, N.C.; Krämer, J.; Polzer, P.; Lohmann, H.; Omran, H.; Wiendl, H.; Göbel, K.; Meuth, S.G. (European journal of paediatric neurology, 2019)
Cognitive impairment (CI) is a critical feature for patients with childhood or juvenile multiple sclerosis (MS). To promote the understanding of CI and to address the impact of different pharmacological treatment strategies on cognitive performance in this patient group. A cohort of 19 patients with therapy-naïve or ß-Interferon-treated juvenile MS completed a comprehensive neuropsychological assessment at initial presentation (baseline) and on average 2.5 years later (follow-up). The assessments were complemented with a neuropaediatric examination and conventional cerebral magnetic resonance imaging (MRI). 9 patients (47%) were impaired in at least one test at baseline (z-score <-1.645 compared with age-adjusted normative data), with the highest impairment frequency in the domains processing speed and attention & executive functions. At follow-up a higher impairment frequency was prominent in those patients whose therapy had not been escalated (N = 13, 69% impaired in at least one test), while cognition was preserved or ameliorated in patients whose treatment had been escalated to highly effective drugs (N = 6, 0% impaired) during the observational period. These group differences at follow-up were not attributable to differences regarding demographics, MRI metrics or cognitive performance at baseline. Our findings confirm that paediatric MS is associated with considerable CI already in early disease stages. Early administration of highly effective treatment may protect from cognitive decline or alleviate CI in juvenile MS, but larger controlled trials are warranted to confirm these preliminary results. •Paediatric patients with MS underwent longitudinal cognitive assessments.•Certain patients were escalated to second-line disease modifying drugs.•These patients showed significantly less cognitive impairment at follow-up.•Highly effective disease modifying drugs may alleviate cognitive impairment.•But larger, placebo-controlled studies are warranted.